Evaluation of some quality indicators in the management of drug acquisitions. Issue 2 (12th March 2012) - Velasco, J.; Olmos, R.; Garcia, O.; Bonillo, C.; Cruz P. De, La; Concepcion, I.; Ramirez, C.; Garcia, R.; Rubia A. De, La
Abstract : Background: According to the Standard Operating Procedure of our pharmacy service, several indicators are being calculated and compared to our historical standards in the absence of relevant literature. Purpose: To evaluate the results of some quality indicators in the management of medicines acquisition in the hospital pharmacy department in 2010. Materials and methods: Indicators and standards to achieve maximum quality in drug procurement have been established in the pharmacy's Standard Operating Procedure. In order to assess the quality of the actions performed in 2010, 4 indicators were calculated: 1. Drugs Rotation Index (RI): Annual procurement value / Stock average value. The standard set is > 12. 2. Efficiency in Procurement Management Index (EPMI): Procurement value / Consumption value. The standard set is ≤1. 3. Drugs Expiry Index (EI): Expired medicine value * 100 / value of acquisitions. Standard < 0.25%. 4. Savings rate (SR) for purchasing management: Value saved on purchases * 100 / Acquisitions value. The standard is to manage to meet or exceed the previous year's standard. Results: Total acquisitions in 2010 were € 50, 801, 425 and 75% were from sole suppliers. The RI for the year of study stands at 21.10. The EPMI was 1. The average annual EI was found to be 0.23%. The annual savings for the management of purchases is 22.19% of total purchases. For the year 2009 this indicator was 17.99%. Conclusions: ▶ The high value obtained for the RI reduces the risk of obsolescence and expiry, and enables less capital to be tied up. However, The authors believe it would be advisable to reduce it to optimise the workload and increase efficiency. ▶ The EPMI value indicates that the capital has remained fixed and the costs of which can be calculated and also allows better management of IR. ▶ The EI reached reflects its relationship with RI. The better the RI indicator, the lower the EI. ▶ Although nearly 75% of drugs were supplied by sole suppliers, the high savings situate procurement management as a strategic element in our department and help the hospital to have those vendors that provide good value for money. ▶ The indicator values obtained suggest high quality management of the acquisitions made in 2010.